Does Business Diversification with Leverage can Improve Firm Performance? - Susanto, Ryan; Widayanti, Rochmi; Irawan, Nico (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The relationship between diversification and leverage strategies on firm performance is complex and varies depending on factors such as industry, country, and type of diversification strategy. This study aims to determine the effect of business diversification and leverage on company performance in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The research population consists of manufacturing companies in the consumer goods sector listed on the IDX during the specified period. Purposive sampling was employed to select 24 companies for the study. The data analysis was conducted using SmartPLS 3.0 software. The findings reveal that both business diversification and leverage exert a positive and significant influence on company performance. Additionally, the study uncovers that the impact of business diversification on company performance is positively moderated by leverage. These results provide valuable insights into the dynamics of diversification and leverage strategies in the context of manufacturing companies in the consumer goods sector in Indonesia.